Yesus Kristus Menurut Orang Papua - Yohanes Kayame (Jurnal Teologi (Journal of Theology), 2019)
This article is pertained to the Papuan Christology that has so far been developed. The writer attempts to reflect and study it based on the Asian Christology. The fundamental question of this study is: Who do you say I am? (cf. Mat 16:15-16). In answering this question, the Papuan Christology becomes the first main point, namely cultural reflection on the concept of salvation and Papuan Christology. The second main point of discussion is that missionary preaching leads Papuans to interpret the western Christology in prayer and liturgy. Based on the analysis of Papuan culture, a number of titles are given to Jesus. From the reciprocal influence between the traditional religion of Papuans about salvation and the missionary preaching on Christian faith the Papuan Christology was born. The present Papuan context requires the study of Christology to respond to the third world challenge. The human right violations in Papua, for instance, is an apparent problem. Thus, a critical study on the Asian Christology has become considerably important. The present synthesis of the Papuan Christology is Jesus the Big Brother Almighty. Jesus Christ was born in Papua as He was born from God the Father all centuries before Him, and due to His Resurrection bound by no time and space as well as His Incarnation as a Human. Jesus as the Big Brother of Papuans fights for some of His Fathers missions in Papua, one of which is that He is sent as a Liberator.